Overview of the clinical implementation of a study exploring social withdrawal in patients with schizophrenia and Alzheimer's disease. (February 2019) - Bilderbeck, Amy C.; Penninx, Brenda W.J.H.; Arango, Celso; van der Wee, Nic; Kahn, René; Winter-van Rossum, Inge; Hayen, Anja; Kas, Martien J.; Post, Anke; Dawson, Gerard R.
Abstract: Trans-diagnostic, domain- or symptom-focused approaches have been heralded as advancing psychiatric research, but relatively few clinical research programmes have been undertaken to leverage their potential. In this manuscript we describe the approach and protocol for an exploratory study, PRISM (Psychiatric Ratings using Intermediate Stratified Markers), that will be conducted to explore the biomarkers in schizophrenia (SZ) and Alzheimer's Disease (AD) that may be related to a common symptom, social withdrawal. Patient participants (N = 72 SZ and N = 72 AD study completers), will complete a series of fMRI, EEG, and behavioural paradigms, as well as contributing blood-derived (e.g. epigenetic) and smartphone data related to social behaviour. Self- as well as caregiver- and researcher-reported assessments will be provided to characterise social withdrawal. Normative data will also be collected from a group of healthy controls (N = 48 study completers), half of whom will be matched in terms of age and gender distribution to the SZ and AD group, respectively. Thus we will explore both differentiation and cross-diagnostic overlap in the biomarkers associated with different levels of social withdrawal in SZ and AD. In this way we aim to provide a deeper understanding of the biological underpinnings of symptomatology common to both disorders, and provide insights into novel treatment targets and future drug development approaches.